Planning and optimisation framework for lubricant supply chain with a focus on spent oil - A circular economy approach - T V Sivanandhini; Seema Unnikrishnan; Vidyadhar V. Gedam (International Journal of Sustainable Engineering, 2021)
Circular Economy (CE) approach is gaining increased attention in recent times. Its high time for developing nations and organizations to adopt the CE approaches in a different sector. The drastically growing oil & gas sector is one of the polluting sectors and needs to adopt CE approaches. Specifically, the spent oil generated by the oil & gas sector is classified as hazardous and needs proper management. The work presents CE approach for spent oil in oil and gas sector via the tactical planning and modeling approach. The study focuses on multi-echelon, multi-product, multi-period mathematical model for tactical planning in a closed-loop lubricant oil supply chain. Questionnaires were designed and distributed among 30 executives working in the oil and gas sector, and their responses were reported. The proposed mathematical model suggests economic feasibility and profitability of re-refine spent oil, given the assumption that end products from regular crude oil and base oil are of the same quality. The survey results also show that waste and by-products are the commonly used items that undergo recycling, followed by packaging material. The approach will aid in the decision-making during transportation, production planning, and inventory control for raw materials and end products.